The Effect of Workload, Work Stress and Motivation on Employee Performance: The Case of Regional Secretariat Office at Ogan Komering Ulu Regency - Lovita, Leshy; Rahayu, Sri; Asiati, Diah Isnaini (International Journal of Marketing & Human Resource Research, 2025)
This study aims to determine: 1) The effect of workload, work stress, and motivation on the performance of employees of the Regional Secretariat of Ogan Komering Ulu Regency; 2) The effect of workload on the performance of employees of the Regional Secretariat of Ogan Komering Ulu Regency; 3) The effect of work stress on the performance of employees of the Regional Secretariat of Ogan Komering Ulu Regency; and 4) The effect of motivation on the performance of employees of the Regional Secretariat of Ogan Komering Ulu Regency. This research is associative. The variables examined are workload, work stress, motivation, and employee performance. The sample consists of 107 employees of the Regional Secretariat of Ogan Komering Ulu Regency, selected through cluster sampling. Primary data were collected using a questionnaire. The data analysis technique employed was multiple linear regression using the SPSS program. The results indicate that (1) workload, work stress, and motivation collectively have a positive and significant effect on employee performance; (2) workload has a positive and significant effect on employee performance; (3) work stress has a positive and significant effect on employee performance; and (4) motivation has a positive and significant effect on employee performance. The coefficient of determination indicates that workload, work stress, and motivation collectively explain 54% of the variation in employee performance. The remaining 46% is attributed to other factors not included in the analysis.